Do patients wish to be involved in decision making in the consultation? A cross sectional survey with video vignettes - McKinstry, Brian (BMJ, 2000)
OBJECTIVE: To determine patients' preferences for a shared or directed style of consultation in the decision making part of the general practice consultation. DESIGN: Structured interview, with video vignettes of acted consultations. SETTING: 5 practices in Lothian, Scotland. PARTICIPANTS: 410 patients (adults and adults accompanying children) attending surgery appointments. MAIN OUTCOME MEASURES: Preference for shared or directed form of video vignette for five different presenting conditions. RESULTS: Patients varied in their preference for involvement in decision making in the consultation. Under multiple regression analysis, patients' preference was found to be independently predicted by the problem viewed (patients presented with physical problems preferred a directed approach), patients' age (patients aged 61 or older were more likely to prefer the directed approach), social class (social classes I and II were more likely to prefer the shared approach), and smoking status (smokers more likely to prefer the shared approach). Those patients who were able to answer (or who thought their doctor's style similar to those in the vignettes) were more likely to describe their own doctor's style as similar to their preferred style. No major association in preference was found with sex, frequency of attendance, or perceived chronic ill health. CONCLUSION: Patients may vary in their desire for involvement in decision making in consultations. Although this variation seems to depend on the presenting problem, age, social class, and smoking status, these associations are not absolute, with large minorities in each group. Doctors need the skills, knowledge of their patients, and the time to determine on which occasions, with which illnesses, and at which level their patients wish to be involved in decision making.